Exposure to traffic-related air pollution and acute bronchitis in children: season and age as modifiers. Issue 5 (9th February 2018) - Bai, Lijun; Su, Xi; Zhao, Desheng; Zhang, Yanwu; Cheng, Qiang; Zhang, Heng; Wang, Shusi; Xie, Mingyu; Su, Hong
Abstract : Background: Acute bronchitis (AB) is one of the principal causes of childhood morbidity. Increasing number of studies has shown that air pollution is an important environmental contributor of respiratory disease. However, evidence so far is scarce regarding the effects of air pollution on childhood AB, and it also remains unclear how the risk of AB will change by season and age. Methods: Data on hospital visits for AB in children, air pollution and meteorological factors from 1 January 2015 to 31 December 2016 were collected in Hefei, China. Time-series analysis was applied to assess the short-term effects of traffic-related air pollution on childhood AB outpatient visits. A Poisson generalised linear regression model combined with a distributed lag non-linear model was used to estimate the relationships, controlling for long-term trends, seasonal patterns, meteorological factors and other possible confounders. Results: We found that an IQR increase in concentrations of nitrogen dioxide, particulate matter <2.5 µm and carbon monoxide significantly increased the daily hospital visits for childhood AB with 4-day cumulative effect estimates (relative risks: 1.03, 95% CI 1.01 to 1.05; 1.09, 95% CI 1.07 to 1.11; 1.07, 95% CI 1.05 to 1.09). Notably, the risk estimates during the cold season are pronounced; however, no significant association was observed during the warm season. Interestingly, children aged 6–14 years were more vulnerable to air pollutants than children aged less than 1 year and within 1–5 years. However, no gender difference was observed. Conclusion: A significant association of traffic-related air pollution and increased department visits for childhood AB was observed, notably in school-age children and during the cold season.